Central visual field sensitivity data from microperimetry with spatially dense sampling - Astle, Andrew T.; Ali, Iram; Denniss, Jonathan (Elsevier, 2016)
Microperimetry, also referred to as fundus perimetry or fundus-driven perimetry, enables simultaneous acquisition of visual sensitivity and eye movement data. We present sensitivity data collected from 60 participants with normal vision using gaze-contingent perimetry. A custom designed spatially dense test grid was used to collect data across the visual field within 13° of fixation. These data are supplemental to a study in which we demonstrated a spatial interpolation method that facilitates comparison of acquired data from any set of spatial locations to normative data and thus screening of individuals with both normal and non-foveal fixation “Methods for normative data comparison in gaze-contigent microperimetry” (Denniss and Astle, 2016) [1].